Informação e inclusão: uma análise das políticas de inclusão digital da Prefeitura de João Pessoa - Lourenço, Briggida Rosely de Azevedo (2011)
The project presents an overview of public information policies in the public administration of the city of João Pessoa, which seek to digitally include the citizens and therefore socially. In this sense it is introduced the question of exclusion / inclusion in Brazil. We comment on the discussions of the information society, public policy information in Brazil. We seck for the opinion of the proponents of existing programs in the Municipality of João Pessoa/PB volated to the importance of digital inclusion. This study will be conducted through a qualitative and exploratory with approachs interviews and content analysis. We believe that for the citizens to be included in the information society, they must have access to the use of ICTs.